(Ne)poštenost večdimenzionalne cene v potrošniških pogodbah - Zgaga, Matevž (Podjetje in delo, 2025)
Multidimensional prices are prices that are not strictly proportional to the quantity of units of goods or service ordered. Most countries address them with detailed rules on price transparency, while there are fewer rules governing their substance. Several recent court decisions are not favourable to this form of pricing in consumer contracts. In this paper, I present legal and economic arguments why contractual terms introducing such pricing are not necessarily unfair.
Keywords: cena; consumer protection; contract law; nepošteni pogoji; pogodbeno pravo; price; unfair terms; varstvo potrošnikov